(untitled) (Interfaces: A Journal of Medieval European Literatures, 2022)
Conference Report of the Fribourg Colloquium 2021 Paradigms and Perspectives of a Comparative Medieval Literature (8-10 September 2021), organised by medieval literature scholars of the Institut d’études médiévales at the University of Fribourg (Switzerland).